Konsep Massa Ekonomis Sebagai Ukuran Kelembaman Pelaku Ekonomi Dalam Ruang Harga (Kajian Mekanika Kuantum Dalam Ekonomi Mikro) - Rifai, Bachtiar; Palupi, Dwi Satya; Rosyid, Muhammad Farchani (BERKALA FISIKA, 2010)
This paper has studied the correlation of economic systems in the market for goods by using the concept of state and the concept of observable in quantum mechanics.Also proposed the concept of economical mass as an economic actor counterparts concept of inertia or inertia in physics.Â Studied the things that determine the mass of a principal economic economical.Â Discussed the possibility of applying the model to market goods with commodities and M N economic actors using the concept of Quantum Many Body Problem. Keywords: Ekonofisika, Applied Physics, Massa economical, Quantum many-body problem